Physical Activity Scale for the Elderly: Translation, Cultural Adaptation, and Validation of the Italian Version. (8th August 2018) - Covotta, Antonio; Gagliardi, Marco; Berardi, Anna; Maggi, Giuseppe; Pierelli, Francesco; Mollica, Roberta; Sansoni, Julita; Galeoto, Giovanni
Abstract : Objective. The aim of the study was to translate and culturally adapt the Physical Activity Scale for the Elderly into Italian (PASE-I) and to evaluate its psychometric properties in the Italian older adults healthy population. Methods. For translation and cultural adaptation, the "Translation and Cultural Adaptation of Patient-Reported Outcomes Measures" guidelines have been followed. Participants included healthy individuals between 55 and 75 years old. The reliability and validity were assessed following the "Consensus-Based Standards for the Selection of Health Status Measurement Instruments" checklist. To evaluate internal consistency and test-retest reliability, Cronbach's α and Intraclass Correlation Coefficient (ICC) were, respectively, calculated. The Berg Balance Score (BBS) and the PASE-I were administered together, and Pearson's correlation coefficient was calculated for validity. Results. All the PASE-I items were identical or similar to the original version. The scale was administered twice within a week to 94 Italian healthy older people. The mean PASE-I score in this study was 159±77.88. Cronbach's α was 0.815 (p < 0.01) and ICC was 0.977 (p < 0.01). The correlation with the BBS was 0.817 (p < 0.01). Conclusions. The PASE-I showed positive results for reliability and validity. This scale will be of great use to clinicians and researchers in evaluating and managing physical activities in the Italian older adults population.